Differentiated Approach to the Treatment of Cough - S.A. Kramarev (Zaslavsky O.Yu., 2013)
The article discusses the types of cough, the causes of this symptom, a lot of attention is paid to the treatment. It is emphasized that at present in non-severe cough WHO recommends to focus on drug-free treatment. At the same time, in the presence in child of non-productive, compulsive cough, which affects the well-being and quality of life of the patient, medication antitussive therapy should be prescribed.